2022
DOI: 10.3390/insects13080718
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Mitogenomics of Flesh Flies: Implications for Phylogeny

Abstract: Flesh flies (Diptera: Sarcophagidae) represent a rapid radiation belonging to the Calyptratae. With more than 3000 known species, they are extraordinarily diverse in terms of their breeding habits and are therefore of particular importance in human and veterinary medicine, forensics, and ecology. To better comprehend the phylogenetic relationships and evolutionary characteristics of the Sarcophagidae, we sequenced the complete mitochondrial genomes of five species of flesh flies and performed mitogenomic compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The circular map of the P. casei mt genome is shown in Figure 1 a and is generally consistent with the mt genomes of eight other Diptera, such as P. megastigmata (15,410 bp) ( Figure 1 b), Bactrocera dorsalis (15,915 bp) ( Figure 1 c), Liriomyza bryoniae (16,183 bp) ( Figure 1 e), and Anopheles oryzalimnetes (15,422bp) ( Figure 1 f). The difference in mt genome length between these five species is mainly due to the differences in the size of the control region (from a minimum of 388bp to a maximum of 1354 bp), as previously observed between Diptera species [ 42 ]. In Diptera, the mt genomes of some species, such as Zeugodacus caudatus (15,311 bp) ( Figure 1 d), Homoneura interstincta (16,351 bp) ( Figure 1 g), and Tropidia scita (15,739 bp) ( Figure 1 f) are arranged differently than most species.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…The circular map of the P. casei mt genome is shown in Figure 1 a and is generally consistent with the mt genomes of eight other Diptera, such as P. megastigmata (15,410 bp) ( Figure 1 b), Bactrocera dorsalis (15,915 bp) ( Figure 1 c), Liriomyza bryoniae (16,183 bp) ( Figure 1 e), and Anopheles oryzalimnetes (15,422bp) ( Figure 1 f). The difference in mt genome length between these five species is mainly due to the differences in the size of the control region (from a minimum of 388bp to a maximum of 1354 bp), as previously observed between Diptera species [ 42 ]. In Diptera, the mt genomes of some species, such as Zeugodacus caudatus (15,311 bp) ( Figure 1 d), Homoneura interstincta (16,351 bp) ( Figure 1 g), and Tropidia scita (15,739 bp) ( Figure 1 f) are arranged differently than most species.…”
Section: Resultsmentioning
confidence: 55%
“…The RSCU of P. casei and P. megastigmata show a similar bias, with only minor differences in the use of a few codons, such as CGC, CUC, and ACG. As with other Diptera, the mt genome of Piophilidae is more biased toward the use of amino acids encoded by codons with A or T in the third position [ 42 ]. The amino acid use frequencies of PCGs in the mt genomes of P. casei and P. megastigmata were counted and showed that the number of 20 amino acids varied, but both had the highest frequency of leucine (Leu) usage, followed by isoleucine (Ile), serine (Ser), and glycine (Gly) ( Figure 4 c,g).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation